2022
DOI: 10.1142/s021812742250047x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Memristor-Based Dynamical System with Chaotic Attractor and Periodic Bursting

Abstract: An autonomous memristive circuit is implemented by an active third-order generalized memristor. The mathematical model is established and the stability of the equilibrium point and divergence are analyzed. Lyapunov exponents and bifurcation analysis demonstrate the complex dynamical behaviors of the system. As an internal parameter of voltage controlled memristor is changed, the system changes from bursting chaos to general chaos, which includes chaotic bursting attractor and periodic bursting attractor. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…When A is fixed at 4 V, and F is set at 1 Hz, 2 Hz, and 5 Hz, respectively, the pinched hysteresis loops of W1 and W 2 are shown in figures 1(a) and (c), when F = 2 Hz is maintained and A is determined as 2 V, 3 V, and 4 V, respectively, the pinched hysteresis loop of W1 and W 2 are shown in figures 1(b) and (d). Obviously, the numerical results indicate that the hysteresis loop pinched at the origin and its area decreases with increasing the frequency or reducing the amplitude [62].…”
Section: A 4d Hr Neuron Model Based On Two Memristors 21 Memristor Mo...mentioning
confidence: 91%
“…When A is fixed at 4 V, and F is set at 1 Hz, 2 Hz, and 5 Hz, respectively, the pinched hysteresis loops of W1 and W 2 are shown in figures 1(a) and (c), when F = 2 Hz is maintained and A is determined as 2 V, 3 V, and 4 V, respectively, the pinched hysteresis loop of W1 and W 2 are shown in figures 1(b) and (d). Obviously, the numerical results indicate that the hysteresis loop pinched at the origin and its area decreases with increasing the frequency or reducing the amplitude [62].…”
Section: A 4d Hr Neuron Model Based On Two Memristors 21 Memristor Mo...mentioning
confidence: 91%
“…The switched system circuit built based on Multisim is shown in figure 23, and the corresponding circuit equation can be written according to the circuit schematic as equation (20). = -…”
Section: Circuit Simulation and Dsp Implementationmentioning
confidence: 99%
“…Han Bao et al proposed a new 5-D twomemristor-based jerk system and studied complex dynamical effects induced by memristor and non-memristor initial conditions therein [19]. Shaohui Yan et al proposed a generalized memristor, constructing a simple ternary chaotic oscillator according to Chua's theory,confirming chaotic bursting and periodic bursting phenomena of the system [20]. Numerous studies have shown that chaotic systems composed of memristors usually exhibit complex nonlinear dynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a significant surge in numerous disciplines dedicated to the examination of the classical Lorenz system [3], generalized Lorenz systems [4] and Lorenz-like systems [5]. These systems include the Chen system [6], the Schr ödinger system [7], the memristor-based dynamical system [8] and others.…”
Section: Introductionmentioning
confidence: 99%